ANALISIS SENTIMEN ULASAN APLIKASI ”ACCESS BY KAI” MENGGUNAKAN ALGORITMA MACHINE LEARNING - Nugroho, Moh Andi Setyo; Susilo, Dahlan; Retnoningsih, Dwi (Politeknik Bisnis Indonesia, 2024)
The trains have become one of the most popular modes of transportation in Indonesia. In line with technological advancements, PT KAI launched an application called